2009
DOI: 10.1001/archpediatrics.2009.196
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Nebulized 3% Hypertonic Saline With Epinephrine in the Treatment of Acute Bronchiolitis in the Emergency Department

Abstract: Setting: Single-center urban pediatric emergency department.Participants: Infants younger than 12 months with mild to moderate bronchiolitis.Interventions: Patients were randomized to receive nebulized racemic epinephrine in either hypertonic or normal saline.Outcome Measures: The primary outcome measure was the change in respiratory distress, as measured by the Respiratory Assessment Change Score (RACS) from baseline to 120 minutes. The change in oxygen saturation was also determined. Secondary outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 26 publications
4
89
1
3
Order By: Relevance
“…This could be an explanation for recent controversial results showing that nebulized 3% HS with epinephrine in the treatment of acute bronchiolitis in an Emergency Department did not improve clinical outcome any more than NS (12). In fact, in this study the enrolled infants were evaluated only for 120 minutes after the nebulisation, without any difference in respiratory distress scores, change in oxygen saturation, rate of hospital admissions and return to the ED (12). As the authors admit, patients received only a maximum of 2 drug doses and respiratory parameters were measured for no longer than 120 minutes (12).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This could be an explanation for recent controversial results showing that nebulized 3% HS with epinephrine in the treatment of acute bronchiolitis in an Emergency Department did not improve clinical outcome any more than NS (12). In fact, in this study the enrolled infants were evaluated only for 120 minutes after the nebulisation, without any difference in respiratory distress scores, change in oxygen saturation, rate of hospital admissions and return to the ED (12). As the authors admit, patients received only a maximum of 2 drug doses and respiratory parameters were measured for no longer than 120 minutes (12).…”
Section: Discussionmentioning
confidence: 90%
“…In a pre-hospital setting, Al-Ansari et al compared the effects of 5% vs 3% HS in addition to epinephrine, showing a better response to the more concentrated solution in term of clinical severity scores (11). More recently, it has been shown that in the treatment of acute bronchiolitis in an emergency department setting, the use of nebulized 3% HS added to epinephrine did not improve clinical outcomes more than normal saline (NS) and epinephrine (12). However, therapies that may contribute to the reduction in hospital stay could potentially greatly reduce health costs related to bronchiolitis (2).…”
mentioning
confidence: 99%
“…7 Since this review, additional studies have evaluated HS in infants with bronchiolitis: 1 in an ambulatory setting, 3 in an emergency department (ED), and 5 in hospitalized patients. 6,[8][9][10][11][12][13][14][15][16] All of these studies have shown a reduction in pulmonary severity scores and/or a trend toward reduced admission rates in the HS group. Of note, all investigations to date have shown HS to be safe, with no patients experiencing decreased oxygen saturation, apnea, or cyanosis after administration of the medication.…”
Section: Discussionmentioning
confidence: 99%
“…Further, most of the previous studies in bronchiolitis have used similar models, by using HS combined with a bronchodilator to demonstrate a clinical improvement. [8][9][10]15,16,21 However, HS appears to be safe when used alone to treat infants with bronchiolitis. 11,12,22 Another limitation is that the modified BSS is not widely used and has not been externally validated.…”
Section: Articlementioning
confidence: 99%
“…Thus the ideal treatment has to decrease submucosal edema and improve mucociliary clearance by restoring the elasticity and viscosity of the mucus. In the last decade, 3% and 5% hypertonic saline (HS) studied in infants with bronchiolitis with good results (8)(9)(10)(11)(12)(13)(14). In the light of cystic fibrosis studies, it was shown that 7% HS increases mucociliary clearance and decreases epithelial edema (15-17).…”
mentioning
confidence: 99%